Analisis Hukum Terhadap Perkawinan Beda Agama Dalam Persektif Hukum Islam - Febrianti Hutagalung; Rizal Sanusi Hasibuan; Sulastri Krisdayanti Sinambela; Sri Hadiningrum (Al Fuadiy Jurnal Hukum Keluarga Islam, 2023)
An interfaith marriage is a marriage between followers of different religions, but because Indonesian society has various religions, they still adhere to their respective religions. Articles 40(c) and 44 of the KHI provide an explanation that non-Muslim women may not marry men. Muslim men, whatever their religion. The research method used by the author is a normative juridical legal research method. Ronnie Hanitiho explains: "The usual legal research is library research, or research on secondary data. What is meant by "1 Secondary data" is data that is already available, such as statutory regulations and academic books, with data collection techniques using library techniques, namely data collection techniques by understanding and studying theories from various literature related to research. The results of the analysis show that the occurrence of marriages of different religions and nationalities is of course a result of social pluralism, way of life and behavior, but marriage is a long-term physical and spiritual bond between a man and a woman, and this bond is established over the long term. long time period of time.